The infrastructure catalyst: analysing the impact of development finance institutions on private infrastructure financing in developing countries - Mishra, A (Centre for the Study of African Economies, 2023)
The widening financing gaps for the Sustainable Development Goals (SDGs) and the Green Energy Transition in developing countries have established an impetus to mobilise foreign private resources for infrastructure. By developing a novel theoretical framework and leveraging a large dataset of infrastructure projects in developing countries from 1989-2022, this analysis investigates the role of Development Finance Institutions (DFIs) in indirectly mobilising private finance. Theoretical analysis demonstrates that DFI participation in a particular country-sector can catalyse private finance by specifically reducing the perceived risks of financing. Empirical analysis assessing the presence and magnitude of mobilisation effects at the extensive margin is consistent with theory on mobilisation. DFI participation is strongly correlated with an increase in the number of commercial foreign banks, total project activity, and the number of projects with at least one commercial foreign bank. Evidence suggests that this effect is amplified by DFI participation induced private financing acting as an independent signal for further private financing. However, the mobilisation effect does not seem to spill over across countries and sectors and does not extend to projects that are entirely financed by commercial foreign financiers. These findings suggest that DFI capital should target infrastructure segments with high growth potential, through project structures that resemble the conditions for private financing and contribute towards creating a pipeline of investable projects in those country-sectors. Immediate policy implications include improving data reporting on current and future projects to bolster demonstration effects and facilitate research on intensive margin mobilisation effects.